2010
DOI: 10.1007/s00415-009-5437-3
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab in the treatment of IVIG-dependent chronic inflammatory demyelinating polyneuropathy

Abstract: Chronic inflammatory demyelinating polyneuropathy (CIDP) is an idiopathic immune mediated neuropathy causing demyelination and conduction block thought to occur as the result of an aberrant autoimmune response resulting in peripheral nerve inflammation mediated by T cells and humoral factors. Diagnosis commonly prompts initial treatment with steroids or intravenous immunoglobulin (IVIG) on which 5-35% subsequently become dependent to maintain function. Despite a number of small scale trials, the role for alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 30 publications
(29 reference statements)
0
38
0
4
Order By: Relevance
“…Her remission lasted for 9 months, at which time she relapsed again and was again given alemtuzumab. She experienced no adverse effects [10,23].…”
Section: Brannagan and Pattersonmentioning
confidence: 92%
See 2 more Smart Citations
“…Her remission lasted for 9 months, at which time she relapsed again and was again given alemtuzumab. She experienced no adverse effects [10,23].…”
Section: Brannagan and Pattersonmentioning
confidence: 92%
“…Of the seven patients, two developed high levels of anti-thyroperoxidase antibodies and one of these two patients developed thyroidstimulating hormone receptor antibodies and Grave's disease [23].…”
Section: Brannagan and Pattersonmentioning
confidence: 99%
See 1 more Smart Citation
“…Scarce information is reported in patients with CIDP. A study in 7 patients pointed to a prolonged remission or partial response in 4 patients [64]. However, 3/7 patients developed an autoimmune condition (high levels of antithyroperoxidase antibodies in 2 patients, 1 of whom was Table 1 Good practice points for treatment of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) [29] For induction of treatment 1.…”
Section: Long-term Therapy For Cidpmentioning
confidence: 99%
“…In a small study, four of seven CIDP patients showed improvement following alemtuzumab; two of these achieved complete remission [67]. An open-label Phase IV clinical trial is currently being initiated to evaluate the impact of alemtuzumab in patients with CIDP (an openlabel trial of alemtuzumab in CIDP).…”
Section: Alemtuzumabmentioning
confidence: 99%